Change in armed conflict: an introduction - Idler, A (SAGE Publications, 2023)
How can we understand change in armed conflict both at the level of the phenomenon as such, as well as within individual conflicts? This Special Issue sets a new agenda on the theme of change in armed conflict. Studying conflict as a dynamic social phenomenon requires embracing interdisciplinarity and methodological pluralism, which this Special Issue facilitates through a shared conceptual framework on five dimensions of change as ‘lingua franca’ across diverse approaches and perspectives. It advances debates through three contributions: by critically assessing pre-existing categories and labels; by accounting for perceptions and experiences; and by scaling analyses across varying units and levels of analysis.